2018
DOI: 10.1007/s10508-018-1150-6
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Disparities in the Prevalence of Suicide Ideation and Attempt Among Bisexual Populations

Abstract: Sexual minorities are at increased risk of suicide; however, it is unclear whether there are within-sexual minority differences in risk across specific sexual identities-notably between bisexual and lesbian/gay subgroups. We therefore conducted a systematic review and meta-analysis to quantify associations between bisexual identity and self-reported suicide ideation and attempt and the moderation of these associations by gender/sex, age, sampling strategy, and measurement of sexuality. Abstracts and full texts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
96
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(115 citation statements)
references
References 104 publications
9
96
2
Order By: Relevance
“…While female gender and older age are robust protective factors for most forms of substance use among heterosexuals, these factors appear to have a diminished, and differential, protective effect among SMs (Green and Feinstein, 2012), as age appears to have a stronger protective effect for gay/lesbian women compared to bisexual women. Overall, our results highlight the importance of examining heterogeneity among SMs, a point emphasized by a recent meta-analysis of SM suicide disparities that found risk to vary with respect to the “three-way intersection” of age, gender, and sexual identity (Salway et al, 2018). …”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…While female gender and older age are robust protective factors for most forms of substance use among heterosexuals, these factors appear to have a diminished, and differential, protective effect among SMs (Green and Feinstein, 2012), as age appears to have a stronger protective effect for gay/lesbian women compared to bisexual women. Overall, our results highlight the importance of examining heterogeneity among SMs, a point emphasized by a recent meta-analysis of SM suicide disparities that found risk to vary with respect to the “three-way intersection” of age, gender, and sexual identity (Salway et al, 2018). …”
Section: Discussionsupporting
confidence: 56%
“…One review found that half of SM youth who come out to their parents experience rejection (Rosario and Schrimshaw, 2013). Bullying, family rejection and identity formation are experiences that are often most acute for SMs in adolescence and young adulthood; during later adulthood, SM individuals may have fully synthesized their identity and established social connections and their own families (Salway et al, 2018), factors which may attenuate risk for substance use. Notably, SM respondents ages 18–25 were born between 1990 and 1998 and are coming of age in the most tolerant social climate to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While SGMA communities can be a haven for some, many SGMA experience discrimination from other SGMA due to intersecting identities related to gender, sexuality, HIV status, race, Indigeneity, and class. Those who are marginalized within SGMA communities are often at increased risk of suicide (Ferlatte et al 2018;Salway et al 2018b). As such, actions to combat oppression within SGMA communities are urgently needed.…”
mentioning
confidence: 99%
“…1 Not bad. Subsequently, I have had the privilege and good fortune to publish two other meta-analytic studies (Grimbos, Dawood, Burris, Zucker, & Puts, 2010;Lalumière, Blanchard, & Zucker, 2000) with colleagues and another one is in the works (Zucker & Aitken, 2018 Puts, McDaniel, Jordan, & Breedlove, 2008;Rooney, Tulloch, & Blashill, 2018;Salway et al, 2019;Schmidt, Babchishin, & Lehmann, 2017;Van Dongen, 2012;Zou & Fan, 2017) and at least two more are in press (Körner, Schaper, Pause, & Heil, in press; Mori et al, in press).…”
mentioning
confidence: 99%